2018
DOI: 10.1038/s41598-018-28347-4
|View full text |Cite
|
Sign up to set email alerts
|

Measuring shared knowledge with group false memory

Abstract: We conducted two experiments to investigate the effects of word list consistency and group collaboration on false memory. Using the DRM (Deese-Roediger-McDermott) paradigm, the first experiment (n = 121) examined false memory in a group; participants collaborated to select keywords using a between-subject condition of a consistent or randomized word list. The proportion of false responses was larger than that of error responses, especially for the consistent word list condition (p < 0.001), and group collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Simple knowledge structures have access to the maximum storage capacity; however, the more complex they become, the lower the storage capacity. Arima et al (2018) showed that false memories increase when they share a knowledge structure. However, the discussion task in the experiment involved the collaborative recognition of a random list of words; it was not a natural group discussion.…”
Section: Group False Memorymentioning
confidence: 99%
“…Simple knowledge structures have access to the maximum storage capacity; however, the more complex they become, the lower the storage capacity. Arima et al (2018) showed that false memories increase when they share a knowledge structure. However, the discussion task in the experiment involved the collaborative recognition of a random list of words; it was not a natural group discussion.…”
Section: Group False Memorymentioning
confidence: 99%